Biodiversity of Vegetation and Flora in Tropical Africa - Catarino, Luís; Romeiras, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
African ecosystems comprise a wealthy repository of biodiversity, with a high proportion of native and endemic plant species, which makes them biologically unique and providers of a wide range of ecosystem services. A large part of African populations, in both rural and urban areas, depend on plants for their survival and welfare, but many ecosystems are being degraded, mostly due to the growing impacts of climate change and other anthropogenic actions and environmental problems. Loss of habitat and biodiversity affects livelihoods, water supply and food security and reduces the resilience of ecosystems in the African continent. The knowledge about the great African plant and ecosystem diversity, and the structure, composition and processes involved in vegetation dynamics, is crucial to promote their sustainable use and to preserve one of the most understudied regions in the world. This Special Issue aimed to gather contributions that update and improve such knowledge.